(untitled) (Revista Latino-Americana de Enfermagem, 2013)
OBJECTIVE: to identify factors which constrain or determine the return to sexual activity in the puerperium. METHOD: exploratory and descriptive study undertaken in a university hospital in the South of Brazil. Fifteen women who had recently given birth, who received a consultation with the nurse in the period August - October 2011, took part in the study. Data was collected after the consultation had finished through semi-structured interviews, in which the women who had recently given birth were asked about the return to sexual activity and the feelings involved in this process. RESULTS: the principal determinant/constraint for return to sexual activity in the post-natal period was the fear of a new pregnancy. Fear of feeling pain, permission from the health professional, shame of their own bodies and changes in libido emerged as constraining and/or determinant factors in the thematic analysis. CONCLUSION: it is considered fundamental for the issue of contraception to be addressed with the woman/couple during the pre-natal consultation, so that there may be opportunities for reflection and dialog prior to the critical time itself.